Signatures of co-translational folding. - Saunders, R; Mann, M; Deane, C (2011)
Global and co-translational protein folding may both occur in vivo, and understanding the relationship between these folding mechanisms is pivotal to our understanding of protein-structure formation. Within this study, over 1.5 million hydrophobic-polar sequences were classified based on their ability to attain a unique, but not necessarily minimal energy conformation through co-translational folding. The sequence and structure properties of the sets were then compared to elucidate signatures of co-translational folding. The strongest signature of co-translational folding is a reduced number of possible favorable contacts in the amino terminus. There is no evidence of fewer contacts, more local contacts, or less-compact structures. Co-translational folding produces a more compact amino- than carboxy-terminal region and an amino-terminal-biased set of core residues. In real proteins these signatures are also observed and found most strongly in proteins of the alpha/beta structural class of proteins (SCOP) where 71 % have an amino-terminal set of core residues. The prominence of co-translational features in experimentally determined protein structures suggests that the importance of co-translational folding is currently underestimated.